Charles Beard and the Constitution : A Critical Analysis - Brown, Robert Eldon, 1907-2001 (Book collections on Project MUSE., 1956)
In this work, Robert E. Brown applies the fruits of modern historical scholarship toward an understanding of Beard's groundbreaking and controversial work. With a perspective of forty years, Brown attempts to separate the valid from the bogus in this work.